Fast minimum loss space vector pulse‐width modulation algorithm for multilevel inverters. Issue 6 (1st June 2014) - Sozer, Yilmaz; Torrey, David A.; Saha, Aparna; Nguyen, Hung; Hawes, Nathaniel
Abstract : This study focuses on developing fast, easily implementable minimum loss space vector pulse‐width modulation (PWM) algorithms for three‐level inverters that can work through extended region of operation into over modulation. A unique way of duty cycle limitation for the maximum dc bus utilisation and the minimum loss PWM techniques is organised in the algorithm in a way to require minimum cycle time from embedded controllers. The developed control algorithm is tested in the Matlab/Simulink environment for the grid interactive inverter. The algorithm is experimentally evaluated on a system developed for a 15 kW grid interactive inverter for a renewable energy application. The simulation and experimental results show that proposed algorithm is very efficient and represents an easily implementable minimum loss space vector PWM algorithm for multilevel inverters.